PREPARATION OF FUTURE SOCIAL TEACHERS TO WORK WITH MENTALLY DISABLED CHILDREN (Pedagogy of Higher and Secondary Education, 2022)
Problems associated with the preparation of social workers to work with mentality retaeded children.
Keywords: social teacher; professionally focuses on training courses